Impaired Axonal Na+ Current by Hindlimb Unloading: Implication for Disuse Neuromuscular Atrophy - Banzrai, Chimeglkham; Nodera, Hiroyuki; Kawarai, Toshitaka; Higashi, Saki; Okada, Ryo; Mori, Atsuko; Shimatani, Yoshimitsu; Osaki, Yusuke; Kaji, Ryuji (Frontiers in Physiology, 2016)
This study aimed to characterize the excitability changes in peripheral motor axons caused by hindlimb unloading, which is a model of disuse neuromuscular atrophy. Hindlimb unloading was performed in normal 6-week-old male mice by fixing the proximal tail by a clip connected to the top of the animal’s cage for 3 weeks. Axonal excitability studies were performed by stimulating the sciatic nerve at the ankle and recording the compound muscle action potential from the foot. The amplitudes of the motor responses of the unloading group were 51% of the control amplitudes (2.2 ± 1.3 mV [HLU] vs. 4.3 ± 1.2 mV [Control], P = 0.03). Multiple axonal excitability analysis showed that the unloading group had a smaller strength-duration time constant (SDTC) and late subexcitability (recovery cycle) than the controls (0.075 ± 0.01 [HLU] vs. 0.12 ± 0.01 [Control], P < 0.01; 5.4 ± 1.0 [HLU] vs. 10.0 ± 1.3 % [Control], P = 0.01, respectively). Three weeks after releasing from HLU, the SDTC became comparable to the control range. Using a modeling study, the observed differences in the waveforms could be explained by reduced persistent Na+ currents along with parameters related to current leakage. Quantification of RNA of a SCA1A gene coding a voltage-gated Na+ channel tended to be decreased in the sciatic nerve in HLU. The present study suggested that axonal ion currents are altered in vivo by hindlimb unloading. It is still undetermined whether the dysfunctional axonal ion currents have any pathogenicity on neuromuscular atrophy or are the results of neural plasticity by atrophy.